FROM ASSESSMENT TO IMPROVEMENT: HOW EVALUATION ASSIST TEACHERS TO IMPROVE TEACHING QUALITY - Dewi, Lia Prasetyana; Khamim, Siti; Lydia; Khatni, Nazar (Al-Mubtadi: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Learning evaluation is an important component in improving the quality of teacher teaching. This study aims to find out how the learning evaluation process is used by teachers at SDN 29 Sungai Mancur to improve their teaching methods and strategies. The approach used was descriptive qualitative with data collection techniques through interviews, classroom observations and documentation studies. The results show that most teachers have used evaluation results, such as daily test scores and student feedback, as reflection material to improve the next lesson plan. Teachers who actively conducted formative and summative evaluations proved to be quicker to adjust their teaching approach to suit students' needs. Some teachers also showed improvement in the use of learning media and classroom management after receiving evaluation-based training. The conclusion of this study is that evaluation, conducted regularly and analyzed appropriately, can be an effective tool in improving the quality of teaching in primary schools. Evaluation is not only a tool for assessing student learning outcomes, but also a means of continuous improvement in the learning process.